Morphology regulation in vascular endothelial cells - Kiyomi Tsuji-Tamura; Minetaro Ogawa (Inflammation and Regeneration, 2018)
Abstract Morphological change in endothelial cells is an initial and crucial step in the process of establishing a functional vascular network. Following or associated with differentiation and proliferation, endothelial cells elongate and assemble into linear cord-like vessels, subsequently forming a perfusable vascular tube. In vivo and in vitro studies have begun to outline the underlying genetic and signaling mechanisms behind endothelial cell morphology regulation. This review focuses on the transcription factors and signaling pathways regulating endothelial cell behavior, involved in morphology, during vascular development.